PERAN BRAND TRUST DALAM MEMEDIASI BRAND AMBASSADOR DAN SOCIAL MEDIA MARKETING TERHADAP PURCHASE DECISION PADA FANS NCT DREAM - Winadi Prasetyoning Tyas, Ari Anggarani; Atalie, Alana Alysia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
This study aims to analyze the influence of brand ambassador and social media marketing on purchase decision with brand trust as a mediating variable among TosTos consumers who are fans of NCT Dream in Bekasi. A quantitative approach was employed using a survey method involving 130 respondents, and data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results reveal that brand ambassador has a positive effect on purchase decision but no significant effect on brand trust. Social media marketing positively affects brand trust but does not have a direct effect on purchase decision. Furthermore, brand trust fully mediates the relationship between social media marketing and purchase decision, but does not mediate the relationship between brand ambassador and purchase decision. This study contributes theoretically to the development of the Stimulus-Organism-Response (S-O-R) model by demonstrating that brand trust as an internal process (organism) plays an important role in bridging the influence of digital stimuli on purchasing behavior. Practically, the results of this study can provide an initial overview for companies in designing digital marketing communication strategies that are more focused on building consumer trust